2020
DOI: 10.1029/2020gl089152
|View full text |Cite
|
Sign up to set email alerts
|

A New Evaluation of the Role of Urbanization to Warming at Various Spatial Scales: Evidence From the Guangdong‐Hong Kong‐Macau Region, China

Abstract: The urbanization impacts on surface air temperature (SAT) change in the Guangdong-Hong Kong-Macau region (GHMR) from 1979 to 2018 are examined using homogeneous surface observations, reanalysis, and remote sensing. Results show that the warming due to urbanization tends to be smaller or insignificant as the spatial scale increases. The urbanization contribution to the local warming can reach as high as 50% in the center of each metropolis, remains high (~25%) in the Greater Bay Area (GBA), and decreases to abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…For example, Lin et al (2020) found that urbanization contributes about 30% of the change in extreme temperature events in urban areas across China. The inconformity might be explained by the existing phenomenon that urbanization contribution tends to be smaller as the spatial scale increase (Chao et al, 2020 To examine the regional differences in the magnitude of urbanization effects, the spatial patterns of urbanization contributions to the changes in CoHot and DayHot characteristics at regional grid scale are shown in Figure 3. The urbanization effects on hot extremes show regional variations, while relatively coherent distributions for the three characteristics of each type of hot extreme are observed.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Lin et al (2020) found that urbanization contributes about 30% of the change in extreme temperature events in urban areas across China. The inconformity might be explained by the existing phenomenon that urbanization contribution tends to be smaller as the spatial scale increase (Chao et al, 2020 To examine the regional differences in the magnitude of urbanization effects, the spatial patterns of urbanization contributions to the changes in CoHot and DayHot characteristics at regional grid scale are shown in Figure 3. The urbanization effects on hot extremes show regional variations, while relatively coherent distributions for the three characteristics of each type of hot extreme are observed.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the impact of inhomogeneities in the SSD time-series on analysis results caused by station relocation, we only selected meteorological stations that have not been relocated. We selected stations with records covering the period 1987-2016, which is a period of solar brightening [12], dramatic warming [20], and rapid urbanization in China [32]. A total of five stations located near Hangzhou City were selected for this study (Figure 1).…”
Section: Data and Preprocessesmentioning
confidence: 99%
“…In general, the impacts of urbanization on climate change can be estimated by comparing the difference between the climatic time-series of urban and rural stations [18][19][20]. This method referred to as urban minus rural (UMR), has been frequently applied in previous urban warming research, with relatively effective and reliable results [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, in reality, the urbanization processes at different times and in different regions are variable, so it is impossible to subdivide the specific degree of contribution of the urbanization bias to the SAT series on temporal and spatial scales. In addition, there are considerable differences in the mechanisms and magnitudes of the impact of urbanization on different temperature elements (Li et al, 2014), despite the possibly limited contribution to regional warming (Chao et al, 2020), while its impact on extreme temperatures are huge (Li and Huang, 2013;Li et al, 2014;Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%